2012
DOI: 10.2146/ajhp110332
|View full text |Cite
|
Sign up to set email alerts
|

Antibiogram compliance in University HealthSystem Consortium participating hospitals with Clinical and Laboratory Standards Institute guidelines

Abstract: Among respondents from 47 UHC hospitals, the compliance rates to four key CLSI recommendations for antibiograms ranged from 64% to 98%. Respondents from 30 hospitals reported significant involvement of pharmacists in compiling, reviewing, and reporting antibiograms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 14 publications
0
24
0
Order By: Relevance
“…Prior published surveys of antibiogram preparation practices have also shown variability in report format and limited uptake of CLSI guidelines (7)(8)(9). Several prior investigators have used self-reported, voluntary surveys to assess compliance with specific CLSI recommendations (7,8,10). A survey of laboratory directors at 494 U.S. acute care hospitals in 2004 reported 60% of responders in compliance with annually compiling, updating, and distributing a facility antibiogram (8).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Prior published surveys of antibiogram preparation practices have also shown variability in report format and limited uptake of CLSI guidelines (7)(8)(9). Several prior investigators have used self-reported, voluntary surveys to assess compliance with specific CLSI recommendations (7,8,10). A survey of laboratory directors at 494 U.S. acute care hospitals in 2004 reported 60% of responders in compliance with annually compiling, updating, and distributing a facility antibiogram (8).…”
Section: Discussionmentioning
confidence: 99%
“…The self-reported compliance rates in a 2009 survey of pharmacy directors in the University Health Consortium were favorable (10). Respondents reported publishing at least annually (98%), eliminating duplicates (89%), not including surveillance cultures (83%), and including at least 30 isolates for each organism (64%) (10). Studies that assessed compliance by direct inspection of antibiograms showed lower adherence than those that used self-reported compliance (9,11).…”
Section: Discussionmentioning
confidence: 99%
“…Prior evaluations have repeatedly demonstrated that stratification of the antibiogram by known risk factors, such as unit (Binkley et al, 2006; Kaufman, Haas, Edinger, & Hollick, 1998; Lalani et al, 2008; Pogue et al, 2011), body site cultured (Green, 2005; Kuster et al, 2008) or relevant patient characteristics (Bosso, Mauldin, & Steed, 2006), may reveal meaningful differences in antibiotic susceptibility patterns. While unit-specific stratification of antibiograms has become increasingly common, a survey of academic and academically-affiliated healthcare systems indicated that only 6% constructed outpatient antibiograms and only 8% constructed pediatric antibiograms (Xu et al, 2012). While outpatient/pediatric antibiograms are not commonly constructed, previous studies suggest that antibiotic susceptibilities among uropathogens do differ significantly between pediatric inpatients and outpatients (Dahle, Korgenski, Hersh, Srivastava, & Gesteland, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…33 These evolving resistance patterns emphasize the importance of understanding the local and regional epidemiology; however, few hospitals report fungal susceptibilities in their antibiograms. 34,35 Correlating antifungal usage with the emergence of antifungal resistance in Candida is beginning to be established. A French multicenter surveillance program evaluated 2,538 candidemia episodes among adults and children over a 7-year period.…”
Section: Emerging Antifungal Resistancementioning
confidence: 99%